See Inside the Universe an Usborne Flap Book - Frith, Alex; Cosgrove, Lee (Usborne London, 2013)
What's the universe made of? Where did everything come from? Lift the flaps in this fascinating book to reveal some of the amazing discoveries that astronomers and physicists have made in their quest to unlock the mysteries of the Universe.